Ethnocultural education of healthy lifestyles and health promotion of students in the educational environment of the university - Nikolai Petrovich Olesov (Universidade Estadual Paulista, 2021)
The article presents ethnocultural education valuing attitude towards healthy lifestyles and health promotion of students in the university in Yakutia. The study aims at the values of tolerance, awareness of its importance for the modern person, whose life activities involve education of a healthy lifestyle and the promotion of health in the educational environment of the university. The study reasonably indicates the need to consider the peculiarities of the educational environment regarding the value attitude to healthy lifestyle and health promotion in educational organizations. The results of the study could be of interest to a wide range of specialists in the field of education. It expands the ideas about the formation of the value attitude to healthy lifestyle and health promotion based on ethnocultural traditions of upbringing of the Sakha people.